Implementation Analysis of Inventory Accounting at CV. Vivace - Joesanna, Aurellia Kevin; Cahyaningtyas, Fadilla (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Inventory management is of paramount importance for trading companies, necessitating meticulous oversight to prevent potential losses. Adhering to inventory accounting principles is crucial, as failure to do so can result in critical errors. PSAK 14, established by the Indonesian Institute of Accountants (IAI), provides a comprehensive framework for these principles. Companies, such as CV Vivace in the entertainment industry, must scrutinize their inventory practices in strict accordance with PSAK 14 to ensure accuracy and compliance. This research adopts a multifaceted approach, incorporating informant interviews, direct observation, and a thorough review of prior studies. The primary objective is to assess CV Vivace's inventory practices, emphasizing the unique challenges faced by companies in the entertainment sector. The study delves into aspects like income generation and methodologies for inventory valuation, setting itself apart from previous research. While CV Vivace aligns with PSAK 14, there is room for improvement. Transitioning to automated systems can enhance efficiency, reducing reliance on manual data entry and mitigating the risk of fraudulent activities. This research anticipates further discussions and in-depth exploration to provide a comprehensive understanding of PSAK 14-related matters, shedding light on the intricacies of inventory management within the entertainment industry.